THE UTILIZATION OF INSTRUCTIONAL MEDIA IN TEACHING ENGLISH TO YOUNG LEARNERS (A Case Study of an Elementary School Teacher in Bandung) - Tanti Sukmahidayanti (Journal of English and Education, 2015)
Many English teachers in Indonesia had difficulty in utilizing instructional media in classrooms. The difficulty was caused by the thought of good media were expensive. Therefore, this study aimed to describe the teacher’s preparation and to explain how the teacher utilized the instructional media in the classroom. This study used qualitative case design and employed observation, interview and data analysis to obtain the data. The result of this study showed that the teacher did two kinds of preparation in utilizing the instructional media, reading the materials and choosing the media. In utilizing the media, the teacher utilized the provided media in the school and did not utilize it optimally due to several challenges, such as limitation of time, difficulty in selecting media, lack of media availability, and teacher’s negative belief towards instructional media and the system. In conclusion, instructional media utilization was not optimally done by the teacher and it needed to be improved. Therefore, the teacher needed to participate in a training program to optimize the teacher’s instructional media utilization.